Chemogenetic Suppression of the Subthalamic Nucleus Induces Attentional Deficits and Impulsive Action in a Five-Choice Serial Reaction Time Task in Mice - Nishioka, Tadaaki; Hamaguchi, Kosuke; Yawata, Satoshi; Hikida, Takatoshi; Watanabe, Dai (Frontiers in Systems Neuroscience, 2020)
The subthalamic nucleus (STN), a key component of the basal ganglia circuitry, receives inputs from broad cerebral cortical areas, and relays cortical activity to subcortical structures. Recent human and animal studies have suggested that executive function, which is assumed to consist of a set of different cognitive processes for controlling behavior, depends on precise information processing between the cerebral cortex and subcortical structures, leading to the idea that the STN contains neurons that transmit information required for cognitive processing through their activity, and is involved in such cognitive control in a direct and dynamic manner. On the other hand, the STN activity also affects intracellular signal transduction and gene expression profiles influencing plasticity in other basal ganglia components. The STN may also indirectly contribute to information processing for cognitive control in other brain areas by regulating slower signaling mechanisms. However, the precise correspondence and causal relationship between the STN activity and cognitive processes are not fully understood. To address how the STN activity is involved in cognitive processes for controlling behavior, we applied Designer Receptors Exclusively Activated by Designer Drugs (DREADD)-based chemogenetic manipulation of neural activity to behavioral analysis using a touchscreen operant platform. We subjected mice selectively expressing DREADD receptor in the STN neurons to a five-choice serial reaction time task, which has been developed to quantitatively measure executive function. Chemogenetic suppression of the STN activity reversibly impaired attention, especially required under highly demanding conditions, and increased impulsivity but not compulsivity. These findings, taken together with the results of previous lesion studies, suggest that the STN activity directly and indirectly participates in cognitive processing for controlling behavior, and dynamically regulates specific types of subprocesses in cognitive control probably through fast synaptic transmission.